2022
DOI: 10.1038/s41467-021-27686-7
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I (TOP1) dynamics: conformational transition from open to closed states

Abstract: Eukaryotic topoisomerases I (TOP1) are ubiquitous enzymes removing DNA torsional stress. However, there is little data concerning the three-dimensional structure of TOP1 in the absence of DNA, nor how the DNA molecule can enter/exit its closed conformation. Here, we solved the structure of thermostable archaeal Caldiarchaeum subterraneum CsTOP1 in an apo-form. The enzyme displays an open conformation resulting from one substantial rotation between the capping (CAP) and the catalytic (CAT) modules. The junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 55 publications
5
30
0
2
Order By: Relevance
“…3). In addition, the tyrosine upstream of the Hinge (position 426) was also found conserved, in agreement with a previous work suggesting that this position interacts with the DNA duplex and guides the motion of the CAP domain upon DNA binding to enable the enzyme closing (Takahashi et al 2022). Within the CAT region, we noticed that near the Linker there are two conserved stretches of around 20 amino acids that flank a poorly conserved region (Fig.…”
Section: Relevant Top1 and Top1mt Sites For Catalytic Activities Tend...supporting
confidence: 91%
See 2 more Smart Citations
“…3). In addition, the tyrosine upstream of the Hinge (position 426) was also found conserved, in agreement with a previous work suggesting that this position interacts with the DNA duplex and guides the motion of the CAP domain upon DNA binding to enable the enzyme closing (Takahashi et al 2022). Within the CAT region, we noticed that near the Linker there are two conserved stretches of around 20 amino acids that flank a poorly conserved region (Fig.…”
Section: Relevant Top1 and Top1mt Sites For Catalytic Activities Tend...supporting
confidence: 91%
“…Previous works have compared Type IB topoisomerases from different species, but often focused on a specific section of the protein or explored only a few animal species [e.g., (Champoux 1998;Takahashi et al 2022;Zhang et al 2004)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SUMOylation sites in human TOP1 and TOP2α and β identified by biochemical and proteomic analyses are shown above their respective domain diagram ( Kanagasabai et al, 2009 ; Hornbeck et al, 2015 ; Matlock et al, 2015 ). TOP1 contains the N-terminal domain (NTD), the capping module (CAP), the catalytic module (CAT), the linker, and the C-terminal domain ( Takahashi et al, 2022 ), which are shown in red, darker green, lighter green, light blue, and yellow, respectively. Its catalytic tyrosine residue is shown in red.…”
Section: Sumoylation In Regulation Of Topoisomerasesmentioning
confidence: 99%
“…In the conformational‐selection binding model, protein conformational changes can occur before the ligand binding, and the binding of the substrate stabilizes a specific conformation of the protein. In induced‐fit binding model, [14] the conformational change is induced by the ligand and occurs upon substrate binding [17] …”
Section: Introductionmentioning
confidence: 99%